Perdagangan Barang Impor di Pulau Sebatik Kabupaten Nunukan Perspektif Undang-Undang Nomor 7 Tahun 2014 Tentang Perdagangan - Sukmawati, Sukmawati; Nasution, Krisnadi (Prodi Tata Negara (Siyasah) IAIN Langsa, 2023)
Basically, no country can create and produce all the goods and services needed to meet the needs of its population. The limited natural resources possessed by each country cause international trade activities. This research aims to analyze the legality of imported goods from Tawau, Malaysia, entering Sebatik Island, Kab. Nunukan. Apart from that, how are the trade arrangements for imported basic necessities for residents of Sebatik Island, Nunukan Regency, regarding imported basic necessities entering Sebatik Island, Nunukan Regency? This research is a normative legal study. The approach used in this research consists of a legal approach and a conceptual approach. The types and sources of legal materials used are primary legal materials, secondary legal materials, and tertiary materials. The results of this research show that, first, trade in imported goods for basic materials in Sebatik is according to Law Number 7 of 2014, trade is according to Government Regulation Number 34 of 2019, and trade is according to the 1970 Border Trade Agreement, which outlines the privileges of border residents, namely Sebatik Island; second, the trade in imported goods that occurs is in accordance with the laws and regulations in force in Indonesia.